TeknoMatika: Technology and product differentiation training to improve mathematics teachers' competence in Pangandaran - Sinta Verawati Dewi; Depi Setialesmana; Linda Herawati; Vepi Apiati; Elis Nurhayati; Siska Ryane Muslim (University of Merdeka Malang, 2024)
This community service program was implemented to address the challenges faced by mathematics teachers in applying differentiated instruction. The program aimed to enhance teachers' competencies in implementing differentiated learning and integrating technology as a teaching aid in mathematics. The training focused on improving teachers' understanding of differentiated instruction, particularly in mathematics education, and equipping them with the skills to utilize technology in the classroom. The methods used included socialization, training, technology implementation, mentoring, and program sustainability. Results showed that 88.2 percent of teachers required technology training, and 80.64 percent expressed interest in participating. Training evaluations revealed an improvement in teachers’ ability to identify students' learning styles and develop technology-based learning media. Teachers reported that Kodular facilitated the creation of interactive and student-centered learning tools. The program successfully enhanced teaching effectiveness, student engagement, and teacher creativity, despite technical challenges such as internet connectivity issues. The TeknoMatika Training has the potential to serve as a model for teacher competency development in other regions, contributing significantly to technology-based educational innovation.